Origin of forbidden reflections in multiferroic Ba2CoGe2O7 by neutron diffraction: symmetry lowering or Renninger effect?. Issue 2 (18th March 2016) - Sazonov, Andrew; Meven, Martin; Roth, Georg; Georgii, Robert; Kézsmárki, István; Kocsis, Vilmos; Tokunaga, Yusuke; Taguchi, Yasujiro; Tokura, Yoshinori; Hutanu, Vladimir
Abstract : Diffraction measurements on multiferroic Ba2 CoGe2 O7 at room temperature with both hot and cold neutrons show that the scattered intensities detected at the positions of reflections forbidden in the tetragonal space group are entirely due to multiple diffraction (the Renninger effect). Abstract : For a symmetry‐consistent theoretical description of the multiferroic phase of Ba2 CoGe2 O7 a precise knowledge of its crystal structure is a prerequisite. In a previous synchrotron X‐ray diffraction experiment on multiferroic Ba2 CoGe2 O7 at room temperature, forbidden reflections were found that favour the tetragonal‐to‐orthorhombic symmetry lowering of the compound [Hutanu, Sazonov, Murakawa, Tokura, Náfrádi & Chernyshov (2011), Phys. Rev. B, 84, 212101]. Here, the results are reported of room‐temperature single‐crystal diffraction studies with both hot and cold neutrons to differentiate between genuine symmetry lowering and multiple diffraction (the Renninger effect). A comparison of the experimental multiple diffraction patterns with simulated ones rules out symmetry lowering. Thus, the structural model based on the tetragonal space group was selected to describe the Ba2 CoGe2 O7 symmetry at room temperature. The precise structural parameters from neutron diffraction at 300 K are presented and compared with the previous X‐ray diffraction results.